Concepts in MDM2 Signaling: Allosteric Regulation and Feedback Loops - Ponnuswamy, Anand; Hupp, Ted; Fåhraeus, Robin (Genes & cancer, 2012)
The function and regulation of MDM2 as a component of a p53-dependent negative feedback loop has formed a core paradigm in the p53 field. This concept, now 20 years old, has been solidified by fields of protein science, transgenic technology, and drug discovery in human cancer. However, it has been noted that a simple negative feedback loop between p53 and MDM2 lacks an intrinsic "activating" step that counteracts this inhibition and permits oscillation of the feedback to occur as p53 is switched on and off. More recent work has identified a solution to the missing piece of the picture that counters the negative feedback loop, which is MDM2 itself. Under conditions of genotoxic stress, MDM2 helps to activate p53 by increasing its rate of protein synthesis. This simple observation makes certain aspects of the p53 response more comprehensible such as why MDM2 is upregulated by p53 early on following DNA damage and how phosphorylation of MDM2 at the C-terminal Ser395 by ATM translates into p53 activation. The latter acts by inducing allosteric changes in the RING domain of MDM2 that expose its RNA binding pocket, support p53 synthesis, and suppress its degradation. This allosteric nature of MDM2 in the C-terminus mirrors the allosteric effects of the binding of small molecules to the p53 interacting pocket at the N-terminus of MDM2, which opens the core domain of MDM2 to central domains of p53, which controls p53 ubiquitination. Thus, the highly allosteric nature of MDM2 provides the basis for dynamic protein-protein interactions and protein-RNA interactions through which MDM2's activity is regulated in p53 protein destruction or in p53 protein synthesis. We discuss these mechanisms and how this information can be exploited for drug development programs aimed at activating p53 via targeting MDM2.